Small-quantity lipid-based nutrient supplements for children age 6–24 months: a systematic review and individual participant data meta-analysis of effects on developmental outcomes and effect modifiers. (29th September 2021) - Prado, Elizabeth L; Arnold, Charles D; Wessells, K Ryan; Stewart, Christine P; Abbeddou, Souheila; Adu-Afarwuah, Seth; Arnold, Benjamin F; Ashorn, Ulla; Ashorn, Per; Becquey, Elodie; Brown, Kenneth H; Chandna, Jaya; et al.
ABSTRACT: Background: Small-quantity (SQ) lipid-based nutrient supplements (LNSs) provide many nutrients needed for brain development. Objectives: We aimed to generate pooled estimates of the effect of SQ-LNSs on developmental outcomes (language, social-emotional, motor, and executive function), and to identify study-level and individual-level modifiers of these effects. Methods: We conducted a 2-stage meta-analysis of individual participant data from 14 intervention against control group comparisons in 13 randomized trials of SQ-LNSs provided to children age 6–24 mo (total n = 30, 024). Results: In 11–13 intervention against control group comparisons ( n = 23, 588–24, 561), SQ-LNSs increased mean language (mean difference: 0.07 SD; 95% CI: 0.04, 0.10 SD), social-emotional (0.08; 0.05, 0.11 SD), and motor scores (0.08; 95% CI: 0.05, 0.11 SD) and reduced the prevalence of children in the lowest decile of these scores by 16% (prevalence ratio: 0.84; 95% CI: 0.76, 0.92), 19% (0.81; 95% CI: 0.74, 0.89), and 16% (0.84; 95% CI: 0.76, 0.92), respectively. SQ-LNSs also increased the prevalence of children walking without support at 12 mo by 9% (1.09; 95% CI: 1.05, 1.14). Effects of SQ-LNSs on language, social-emotional, and motor outcomes were larger among study populations with a higher stunting burden (≥35%) (mean difference: 0.11–0.13 SD; 8–9 comparisons). At the individual level, greater effects of SQ-LNSs were found on language among children who were acutely malnourished (mean difference: 0.31) at baseline; on language (0.12), motor (0.11), and executive function (0.06) among children in households with lower socioeconomic status; and on motor development among later-born children (0.11), children of older mothers (0.10), and children of mothers with lower education (0.11). Conclusions: Child SQ-LNSs can be expected to result in modest developmental gains, which would be analogous to 1–1.5 IQ points on an IQ test, particularly in populations with a high child stunting burden. Certain groups of children who experience higher-risk environments have greater potential to benefit from SQ-LNSs in developmental outcomes. This trial was registered at www.crd.york.ac.uk/PROSPERO as CRD42020159971.